Proposed device for improving meaningful verbal communication for children with autism - Hosseinioun, Asiehsadat (2022)
Education is one of the essential tools for all aspect of life. Every day, everybody uses their experience mixed with knowledge which comes from education and learning to leave better and have a wonderful life. How to speak, how to take someone attention, how show our work and etc are the first, small and easy communication method that everybody uses for daily life but imagine someone without any of this knowledge. It means that if someone does not know or doesn’t learn how to start a small conversation and take the attention, probably will face some difficulty in life. Kids with autism can be one of these group people. The purpose of this study is to analyses the knowledge and implementation of a suitable approach for children with autism to improve their language delay and speech problem, which is related to communication and behaviour patterns. The aim of this study is to improve kids with autism who has speech difficulty by proposing the idea of a new device to increase their communication, social skills and behaviour pattern. The main function of improving communication and social skills is to enhance the ability or the skill of speaking includes language. The study identified a current method to practice speaking with kids to improve the ability to talk, and besides that, to increase the patterns of behaviour. The method used in this research is observation, interview and case study. The idea of this device is built for Kids with mild autism who might be non-verbal (speechless) because of a lack of communication or impairment in social skills. The researcher collected the data while she was working with special kids as an assistant teacher by using case study and observation methods to find the gaps in their speaking, communication, and behaviour patterns. This achievement can help by understanding better in theory of mind. Theory of mind shows that how a mind can control in specific subject and part. The result is the impaired a kid with mild autism’s ability to communicate and social skills. Thus, it shows the advantage of talking to others and increases the ability of communication by user experience. The researcher hopes that the findings will propose the factor which helps to the stakeholder and establishing directions for supporting kids with autism spectrum disorder (ASD) in the future.